Embodying Worldview: How Dance Creates Common Ground - Kallsen, Nicole (The ecumenical review, 2021)
While many scholars conclude that increased artistic contact between religions facilitates cross-cultural interaction, their analysis stops there. This paper aims to demonstrate the artistic gap in modern interreligious dialogue. To combat the lack of specificity of different art forms’ impact, the paper considers how dance, by communicating values through the physical human body, is an artistic mode of dialogue. Dance in Hinduism, in the Church of Jesus Christ of Latter-day Saints, and in nondenominational Christianity is examined regarding their scriptural and socio-cultural expression. Given dance’s multicultural presence, modern scholars need to increase publications that analyze this art’s impact on interreligious dialogue.